Prevalence of Bombay phenotype among Bangladeshi ‘O’ blood group population - Islam Shaheen, Sheikh Saiful; Khatun, Ayesha; Rahman, Atiar; Sonia, Farah Anjum; Fedous, Jannatul (International Journal of Research in Medical Sciences, 2024)
Background: The Bombay blood group, a rare type often confused with ‘O’, poses a critical transfusion risk, requiring specific compatibility with Bombay (Oh) blood. With a lack of data in Bangladesh, this study aimed to establish a comprehensive database for the rare Bombay phenotype, crucial for transfusion safety. Objective was to determine the frequency prevalence of Bombay phenotype among ‘O’ blood group individuals. Methods: A cross-sectional study conducted at Bangabandhu Sheikh Mujib Medical University from January 2020 to June 2021 involved, aseptic collection of 3 ml venous blood sample, with forward and reverse blood grouping revealing a ‘O’ phenotype. Utilizing anti-H lectin resolved discrepancies and confirmed the absence of ‘H’ antigen in individuals with Bombay blood groups. Blood samples of Bombay phenotype individuals showed the following reactions: anti-A (-), anti-B (-), anti-AB (-), anti-H (-), A cells 4+, B cells 4+, O cells 4+. Results: Among 10,000 individuals with apparent blood group ‘O’, 99.97% were identified as ‘O’ blood type, while only 0.03% exhibited the rare Bombay blood group. ABO and Rh-D blood group frequencies varied over the study period, with B +ve at the highest (28.31%) and AB -ve at the lowest (0.21% to 0.23%). Overall, O +ve had the highest frequency (97.29%), and Bombay blood group was rare, with ‘O’ dominating at 99.97%. Conclusions: The study identified a 0.03% prevalence of the Bombay phenotype. Due to its potential confusion with ‘O’ blood group, transfusing ‘O’ blood to Bombay individuals carries a substantial risk of severe hemolytic reactions, including fatal consequences.